Understanding electrochemical capacitors with in-situ techniques. (October 2021) - Pal, Bhupender; Yasin, Amina; Kaur, Rupinder; Tebyetekerwa, Mike; Zabihi, Fatemeh; Yang, Shengyuan; Yang, Chun-Chen; Sofer, Zděnek; Jose, Rajan
Abstract: Understanding the charge (energy) storage process in electrochemical capacitors (ECs) is crucial for continuous performance enhancement of the billion-dollar charge storage industry. Charge storage mechanism in materials discovery/property manipulation experiments are routinely speculated from cyclic voltammetry (CV), galvanostatic charge – discharge cycling (CDC), and electrochemical impedance spectroscopy (EIS) experiments, but with ambiguities. Herein, with reference to charge storage in ECs, areview and discussion on the usefulness and the experimental set-up of in-situ analytical techniques in literature, viz. in-situ nuclear magnetic resonance spectroscopy, in-situ infrared spectroscopy, in-situ X-ray diffraction, and electrochemical quartz crystal microbalance are detailed. The in-situ characterization techniques probe the structural or weight changes in the material as the device is charged or discharged. This time-resolved structural or weight changes helps to determine the charge-discharge process in the device or electrode in the presence of the electrolyte as a function of applied voltage. The studies so far reveal that in an EC electrode with porous carbon, its pores are occupied with electrolyte ions complementary to the surface charge even in the absence of an applied potential, charging the device lead to counter ion adsorption, co-ion desorption and ion exchange in the electrodes. However, research gaps such as the chemical nature of the accessible and inaccessible storage sites, the volume distribution of charge storage, understanding of the appropriation of the charge adsorption at the required sites are yet to be understood. Further requirements to understand the charge storage mechanisms in different electrodes have also been explored. Highlights: Energy storage mechanisms in electrochemical capacitors through in-situ techniques are reviewed. The in-situ NMR, IR, X-ray, and electrochemical quartz crystal microbalance techniques are reviewed. Processes untraceable in conventional measurements canbe identified by the in-situ techniques. Charge accumulation at zero applied field, counter ion adsorption, co-ion desorption, and ion exchange can be tracked. A critical analysis on techniques is drawn and initiations required for future endeavors are highlighted.